Proton Magnetic Resonance Reveals High-Spin Iron (II) in Ferrous Cytochrome P450(cam) from Pseudomonas putida - Keller, Regula M. (1972)
High-resolution proton nuclear magnetic resonance spectra were studied in D(+)-camphor-saturated solutions of ferric and ferrous cytochrome P450(cam) from Pseudomonas putida, and of the cyanide complex of ferric P450(cam). In all these compounds several hyperfineshifted resonances of the heme group could be detected. In the ferrous protein, these resonance lines, which exhibit a Curie-type temperature dependence in the range of 5-28°, indicate the presence of high-spin iron (II). It is suggested that the iron (II) in ferrous P450(cam) might be pentacoordinated, as in other hemoproteins that can reversibly bind molecular oxygen and carbon monoxide.